A trajetória da banda filarmônica Argemiro Ribeiro da Cunha, na cidade de São Valério – TO - Malheiro, Eunice Correia (Universidade Federal do Tocantins, 2024)
This research sought to identify how the formation process of the band Argemiro Ribeiro da Cunha took place, in São Valério, a city in the interior of the state of Tocantins. What was its period of operation, what were the perspectives for its continuity and what contributions and/or transformations occurred in the lives of the people who participated in the project. As a general objective, there was the intention to highlight the role of bands as an element in the formation of musicians and in the social transformation of individuals. The work was based on research such as those carried out by Binder (2006), Salles (1985), Costa (2010; 2011) and Vieira (2013), who studied blow formations in our country under different aspects. The research used the case study as a strategy, a methodology that seeks to report or bring accurate information about a specific case, with the objective of contributing to a better understanding, facilitating decision-making, clarifying the reason for something, or even reporting certain results. The procedures for data collection were: a) interviews with former participants of the group, so that they could report their musical trajectory, as well as the importance of music for each one; b) collection of information from documentary records at the City Council; c) interview with the former conductor (Wada Francyel) so that he could talk about his work; d) interviews with the former mayor and the former secretary of culture. Through the results obtained, it was possible to know the trajectory of the musical group, an example that is similar to so many other cities, cases and bands existing throughout the country.